New Erbium Doped Antimony Glasses For Laser And Glass Amplification - Tioua, B.; Soltani, M. T.; Hamzaoui, M.; Baazouzi, M. (University of Eloued جامعة الوادي, 2012)
Because of the special spectroscopic properties of the rare earth ions, rare earth doped glasses are widely used in bulk and fiber lasers or amplifiers. The modelling of lasers and searching for new laser transitions require a precise knowledge of the spectroscopic properties of rare earth ions in different host glasses. In this poster will offer new doped erbium glasses synthesized in silicate crucibles were obtained in the combination Sb2O3-WO3-Na2O. Several properties are measured and correlated with glass compositions. The absorption spectral studies have been performed for erbium doped glasses. The intensities of various absorption bands of the doped glasses are measured and the Judd-Ofelt parameters have been computed. From the theory of Judd-Ofelt, various radiative properties, such as transition probability, branching ratio and radiative life time for various emission levels of these doped glasses have been determined and reported. These results confirm the ability of antimony glasses for glass amplification.
Articale in Journal of fundamental and Applied Sciences Vol. 04 N. 01
Keywords: antimony glasses, fiber lasers, amplifiers.